2018
DOI: 10.1111/1744-9987.12753
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Serum Potassium Levels and Risk for All‐Cause Mortality in Patients With Chronic Kidney Disease: A Systematic Review and Meta‐Analysis

Abstract: Dyskalemia is a risk factor for mortality in patients without CKD, but the effect of hypokalemia in patients with CKD remains uncertain. PubMed, Embase, Cochrane, and Ovid databases were searched from inception to December 31, 2017 for studies that reported allcause and cardiovascular mortality or events in patients with CKD (any stage). Pooled hazard ratios (HR) and corresponding 95% CI were calculated. A total of 11 clinical studies enrolling 57 234 subjects with CKD were included in the meta-analysis. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…An increase in the in-hospital short-term morbidity-mortality was observed in patients with potassium levels <3.5mmol/L, a finding also observed in another ED study [35] as well as in myocardial infarction patient cohorts [8] and in both hypertensive [33] and chronic HF [29] patients or in meta-analysis [9]. In specific population, as our results, Zhang et al [7] demonstrated in meta-analysis that hypokalemia (<3.5mEq/L) was significantly associated with higher mortality risk among patients with CKD and dominant among women. Zhang et al also found that serum K within 3.5-4.0mEq/L among CKD patients was associated with increased all-cause risk.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…An increase in the in-hospital short-term morbidity-mortality was observed in patients with potassium levels <3.5mmol/L, a finding also observed in another ED study [35] as well as in myocardial infarction patient cohorts [8] and in both hypertensive [33] and chronic HF [29] patients or in meta-analysis [9]. In specific population, as our results, Zhang et al [7] demonstrated in meta-analysis that hypokalemia (<3.5mEq/L) was significantly associated with higher mortality risk among patients with CKD and dominant among women. Zhang et al also found that serum K within 3.5-4.0mEq/L among CKD patients was associated with increased all-cause risk.…”
Section: Plos Onesupporting
confidence: 89%
“…Potassium disturbances are common and have been associated with increased mortality in several populations, namely in those with diabetes [1][2][3], chronic kidney disease (CKD) [2][3][4][5][6][7], myocardial infarction (MI) [8,9], hypertension [9,10] and heart failure (HF) [2,3,6,9,[11][12][13][14]. In these populations, potassium levels have been associated with outcomes in a U-shaped manner, where both hypo-and hyperkalemia portend worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Increased fruit and vegetable intake in the range commonly consumed is associated with a reduced risk of stroke (He et al 2006). The protective effects of fruit and vegetables on stroke prevention have a strong biological basis, including the fact they are rich sources of dietary K. The positive effects of K on human health extend beyond blood pressure and heart disease to include reduction in osteoporosis (Lambert et al 2015), insulin-resistant diabetes (Ekmekcioglu et al 2016), kidney disease (Zhang et al 2019), ulcerative colitis and Crohn's disease (Khalili et al 2016), and obesity and metabolic syndrome (Cai et al 2016).…”
Section: Human Nutrition and Healthmentioning
confidence: 99%
“…An observational study of patients in a large Swedish healthcare system found that hypokalemia occurred in 49,662 (13.6%) of 364,955 individuals 1 . Furthermore, hypokalemia has been associated with increased mortality for patients with various conditions, such as diabetes, chronic kidney disease, myocardial infarction, and heart failure 2–6 …”
Section: Introductionmentioning
confidence: 99%